Law, Security and Democracy - Sedrakyan, Artyom (Bulletin of Yerevan University C: Jurisprudence, 2022)
Systemic relations between law and security, security and liberty as well as democracy are analyzed in this article.It is assessed that there is a grand clash between security interests and democratic values and that this exists in each and every aspect of public life. The aim is to study hypothetical and real consequences of this clash; understand whether it is possible to find the necessary balance (legal equilibrium) of those interests and values.The author concludes that democracy is not opposed to security. You can always find the “golden mean”. And here the role of law as a unique tool (a regulator) is hardly to be overestimated.
Keywords: law; liberty; democracy; human rights; security; national security; defence of the state; time of emergency; legal equilibrium